Business Cycle Turning Points and Local Labour Markets - Karl Taylor; Soumya Bhadury; Jane Binner; Anandadeep Mandal (Institute of Labor Economics (IZA), 2024)
In this paper we consider the predictors of the business cycle in Great Britain, where the claimant count and unemployment rate are found to be key indicators associated with turning points. Next, we consider at a micro-economic level, using disaggregated local authority level data, a number of local labour market issues: (i) the determinants of the claimant count and unemployment rate (both highly correlated with the cycle); (ii) local level economic resilience; and (iii) the likelihood of different states of regional vulnerability. Benefit generosity, unit labour costs and state dependence (hysteresis) are key drivers of local labour market performance.
Keywords: E24; E32; J20; R10; R23; 330; business cycle dating; local labour markets; resilience; regional vulnerability